Finite element modelling of the effect of temperature and neutron dose on the fracture behaviour of nuclear reactor graphite bricks - Wadsworth, M.; Kyaw, Si Thu; Sun, Wei (Elsevier, 2014)
Graphite moderator bricks used within many UK gas-cooled nuclear reactors undergo harsh temperature and radiation gradients. They cause changes in material properties of graphite over extended periods of time. Consequently, models have been developed in order to understand and predict the complex stresses formed within the brick by these processes. In this paper the effect of irradiation temperature and neutron dose on the fracture characteristics, crack initiation and crack growth are investigated. A finite element (FE) mechanical constitutive model is implemented in combination with the damage model to simulate crack growth within the graphite brick. The damage model is based on a linear traction–separation cohesive model in conjunction with the extended finite element method for arbitrary crack initiation and propagation. Results obtained have showed that cracks initiate in the vicinity of the keyway fillet of the graphite brick and initiation time accelerates with higher temperatures and doses.